2017
DOI: 10.13080/z-a.2017.104.035
|View full text |Cite
|
Sign up to set email alerts
|

Meat quality of different beef cattle breeds fed high energy forage

Abstract: Please use the following format when citing the article: Jukna V., Jukna Č., Prusevičius V., Meškinytė-Kaušilienė E., Pečiulaitienė N. 2017 AbstractThe aim of this study was to investigate the changes in meat quality characteristics of different beef cattle breeds fed high energy forage. The study included 200 days old uncastrated beef cattle of the following breeds: Limousin, Charolais, Angus, Hereford and Simmental. Feeding and housing conditions for bulls were the same. Animals were given a certain amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
3
3
0
Order By: Relevance
“…Low intramuscular fat content of red deer found in the present study is in agreement with the review of Daszkiewicz and Mesinger [21]. Hoehne et al [22] have reported higher intramuscular fat means and their range for Charolais and German Holstein bulls than for Aubrac bulls, however, low IMF for Aubrac is consistant with the fi ndings of Jukna et al [23] for the same breed. In contrast to beef and meat of red deer, the meat of Lithuanian Vishtines goose showed the highest fat content.…”
Section: Intramuscular Fat Contentsupporting
confidence: 93%
“…Low intramuscular fat content of red deer found in the present study is in agreement with the review of Daszkiewicz and Mesinger [21]. Hoehne et al [22] have reported higher intramuscular fat means and their range for Charolais and German Holstein bulls than for Aubrac bulls, however, low IMF for Aubrac is consistant with the fi ndings of Jukna et al [23] for the same breed. In contrast to beef and meat of red deer, the meat of Lithuanian Vishtines goose showed the highest fat content.…”
Section: Intramuscular Fat Contentsupporting
confidence: 93%
“…In a Lithuanian study using purebred bulls slaughtered at 500 days of age (Jukna et al, 2017), compared to the results of our study, a lower dry matter content was obtained in M. longissimus muscle samples of all three breeds (AA bulls -24.26±0.11%, HF bulls -25.17±0.54%, LI bulls -24.50±0.26%). Like our study, the lowest total fat and the highest protein content were obtained in LI breed bull meat.…”
Section: Chemical Composition and Ph Value Of M Longissimus Muscle In...supporting
confidence: 58%
“…It has been shown that bulls are more sensitive to pre-slaughter handling than heifers and steers, and this can lead to inappropriate pH value (Bures & Barton, 2012;Cafferky et al, 2019). However, there are several studies confirming that AA, HF and LI breed bulls produce meat with a lower pH value than in our study (Jukna et al, 2017;Moran et al, 2019;Pesonen, Honkavaara & Huuskonen, 2013a).…”
Section: Chemical Composition and Ph Value Of M Longissimus Muscle In...supporting
confidence: 43%
“…Different breeds of animals have different economic and biological features that were imparted to them in the process of their creation by selection. The size and quality of meat yield are determined by the ability of animals to use nutrients from the fodder to develop of muscle and fat tissues (Pesonen et al, 2015;Jukna et al, 2017). When specialized meat breeds were created, the aim was to obtain animals with well-developed muscular tissues that would have a wide and deep chest and well-rounded legs.…”
Section: Slaughtering Qualitiesmentioning
confidence: 99%